CFD simulation of single‐phase suction head and power consumption in a delta impeller pump–mixer. Issue 6 (20th September 2016) - Huang, Yi; Wu, Bin; Chen, Kui; Zhu, Jiawen; Ji, Lijun; Wu, Yanyang; Shen, Zujun
Abstract: Agitation is one of the greatest challenges in the computer simulation, which is a common operation in mixer–settlers. In the present work, hydrodynamic characteristics of delta impeller pump–mixers have been studied using computational fluid dynamics (CFD) simulations. Sliding mesh approach has been used for the modeling of interaction between static tank and rotating impeller. Standard k–ε turbulence model was adopted. The effect of different geometrical parameters including off‐bottom clearance, impeller diameter, number of blades and height of suction orifice on suction head and power consumption characteristics has been investigated. Low off‐bottom clearance and high suction orifice location were found beneficial to suction increase without extra power input. Scale‐up study has also been carried out at two different vessel sizes. CFD simulation results have been validated and agree with literature and experimental data. Optimum geometry of pump–mixer has been proposed, and new delta impeller designs have been proved better than the original one in pumping capacity. Scale‐up study shows a close agreement of power number and head number of different geometric scales and confirms the validity of CFD simulation in scale‐up of the delta impeller for industrial‐scale application. Copyright © 2016 Curtin University of Technology and John Wiley & Sons, Ltd.